Is maximal heart rate decrease similar between normobaric versus hypobaric hypoxia in trained and untrained subjects? - Mourot, L.; Millet, G. P. (High Altitude Medicine & Biology, 2019)
Mourot, Laurent and Grégoire P. Millet. Is maximal heart rate decrease similar between normobaric versus hypobaric hypoxia in trained and untrained subjects? High Alt Med Biol. 19:000-000, 2018.—(n = 187) We compared the decrease in maximal heart rate (HRmax) from normoxia to normobaric (NH) and hypobaric (HH) hypoxia, respectively, in trained and untrained subjects. HRmax data in normoxia and NH (n = 55) or HH (n = 26) were collected from 81 publications. No study directly compared HRmax in NH and HH. Concomitant arterial oxygen saturation (SaO2) and HRmax data were found in 60 studies. Overall, the results showed that the higher the desaturation, the greater the decrease in HRmax. Since desaturation appeared to be slightly higher during HH versus NH and was higher in trained than in untrained subjects, the decrease in HRmax tended (p = 0.07) to be higher in trained subjects in HH than in NH (e.g., -12.7 bpm vs. -8.6 bpm at 4000 m), whereas in untrained subjects the difference was negligible (-9.9 bpm vs. -8.3 bpm). To conclude, when compared with normoxia, the decrease in HRmax was slightly higher in HH than in NH in trained subjects. However, this result has to be confirmed and from a practical point of view, one may question the significance of this difference as well as the relevance of using different HR values for prescribing training intensity during exercise performed in NH or in HH.